A STAKEOHOLDER ANALYSIS OF THE RESEARCH AND SURVEILLANCE ACTIVITIES OF THE INSTITUTE FOR ANIMAL HEALTH - Okala, Wilson (2009)
This paper seeks to investigate stakeholder perspectives of the research and surveillance activities of the Institute for Animal Health. Using frameworks from stakeholder theory and strategy, and qualitative investigatory techniques the study finds that while the reputation of the Institute for Animal Health remains outstanding in the international community, it is still suffering locally from the FMD outbreak of 2007, and this is made worse by the lack of effective communication with its stakeholders, lack of effective project management and poor commercialization efforts. The study finds that stakeholders who know about what the Institute does believe it to between very good and outstanding while those who have a poor perception of its science, programmes, compliance with standards and guidelines and image do so because they have little or no information. The paper concludes and recommends that the Institute of Animal Health will boost its reputation with stakeholders by improving communication and expanding its media angle to cover the general public. The communication must be in the language that stakeholders will understand and must contain information about what it does and recent successes. It will need to increase dialogue with stakeholders to better understanding their objectives and key performance drivers; it will also need to project manage its activities and increase technology transfer efforts